If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2 = -1x + -8 Reorder the terms: 2 + x = -1x + -8 Reorder the terms: 2 + x = -8 + -1x Solving 2 + x = -8 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 2 + x + x = -8 + -1x + x Combine like terms: x + x = 2x 2 + 2x = -8 + -1x + x Combine like terms: -1x + x = 0 2 + 2x = -8 + 0 2 + 2x = -8 Add '-2' to each side of the equation. 2 + -2 + 2x = -8 + -2 Combine like terms: 2 + -2 = 0 0 + 2x = -8 + -2 2x = -8 + -2 Combine like terms: -8 + -2 = -10 2x = -10 Divide each side by '2'. x = -5 Simplifying x = -5
| -1v+3v=4 | | 4-2x+4z+2=23.6 | | 1v+3v=4 | | y^2+x^2=40000 | | http://c-4/5=-5/6 | | 6p+4c=35 | | 3/2•4/3 | | 6*y=2/3 | | 4c=35-6p | | -3.7(-5x+2)-1.3x= | | 3s+2(5s-1)=56.50 | | 7(6a+4b+8c)= | | 6/11x+4=2/11+16 | | 4=(3x-2) | | 12=3z | | 2x(5x+23)=x(11x+27) | | 2x(8x+1)=x(15x+10) | | -2.5(m-8)=14-1.5 | | 1/2x-1/2x | | 9(x-8/9)=9(1)9(-x/8) | | yz(xz-x)=xy(z^2-x)-3x | | m=((n)/14) | | 8(2r-3)-r=3(3r-2) | | 100x/20=x | | 100x-20=x | | 100x+20=x | | 24-7x=-10x | | (2+3)x(9-5)= | | (4/3x-1/3)4 | | 13xy-9xy= | | 2x^5-x^4-1=0 | | 1y=0.5x |